Διά βίου μάθηση και δυνατότητες εκπαιδευτικής επανένταξης ατόμων που κάνουν κατάχρηση ουσιών. - Anna Tsiboukli (Educational Review: The journal of the Hellenic Educational Society, 2021)
Social exclusion is a complex process. Tackling social exclusion through Lifelong learning is often an unattainable goal. Lifting the conditions of exclusion through Lifelong learning programmes, requires an understanding of the special features and characteristics that each group holds. The current paper focuses on the people who abuse drugs and explores the possibilities of reconnecting them with education, through Lifelong learning programmes. School dropout is related with early onset of substance use and social exclusion. For those who seek drug free treatment, reconnecting with education and learning is plausible. However, it requires experiential learning methods, a facilitating environment, and the development of a trusting relationship between trainers and trainees. In this way, it is possible to increase participation in Lifelong learning programmes, to create meaning in education and to achieve UNESCO’s goal of Lifelong learning as a new human right.